2020
DOI: 10.1088/1361-6463/abb8fe
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of film crystallinity and morphology on charge carrier concentration-dependent hole mobility in pentacene thin-film transistors: advantages of high deposition rate

Abstract: The combined effect of deposition rate and substrate temperature on the film crystallinity, morphology, and electronic properties of pentacene is studied. It is shown that the channel mobility in polycrystalline pentacene thin-film transistors is relatively immune to substrate temperature, and the films offer good hole mobility when grown at a high rate. This is advantageous when high throughput with low deviation in electrical parameters over devices are required. The surface morphology is characterized by at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…[47] In fact, the architecture of the film strongly influences the transport properties of the semiconducting layer, as revealed by the effect of film crystallinity and morphology on charge carrier mobility in thin film transistors of pentacene, where it was shown that a good hole mobility could be obtained once the film was deposited at high rate. [50] This observation is fully consistent with the idea that at high rate we have a 2D growth regime, [47] with a corresponding poor interlayer correlation perpendicular to the dielectric interface. Besides, in our conditions of pentacene growth, [47] high rates yield 2D nucleation, leading to a quasi-layer-by-layer growth, forming continuous films, more suitable for charge transport.…”
Section: Pentacenesupporting
confidence: 88%
See 3 more Smart Citations
“…[47] In fact, the architecture of the film strongly influences the transport properties of the semiconducting layer, as revealed by the effect of film crystallinity and morphology on charge carrier mobility in thin film transistors of pentacene, where it was shown that a good hole mobility could be obtained once the film was deposited at high rate. [50] This observation is fully consistent with the idea that at high rate we have a 2D growth regime, [47] with a corresponding poor interlayer correlation perpendicular to the dielectric interface. Besides, in our conditions of pentacene growth, [47] high rates yield 2D nucleation, leading to a quasi-layer-by-layer growth, forming continuous films, more suitable for charge transport.…”
Section: Pentacenesupporting
confidence: 88%
“…Besides, in our conditions of pentacene growth, [47] high rates yield 2D nucleation, leading to a quasi-layer-by-layer growth, forming continuous films, more suitable for charge transport. [14,50,51] On the contrary, low deposition rates yield a 3D growth, leading to ill-connected grains. [50] These findings have their counterpart in the two upper spectra of Figure 1a, where the TF spectrum at low rate exactly matches that of the HT bulk phase, and is therefore labelled 3D.…”
Section: Pentacenementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a very recent paper that appeared in the literature has thoroughly studied the effect of film crystallinity and morphology on the charge carrier mobility in thin film transistors of pentacene. 84 A good hole mobility is indeed obtained once the film is deposited at a high rate, an observation that fully agrees with our view of the actual formation of a 2D film with a corresponding low inter-layer correlation close to the dielectric interface, where charge transport is more efficient. 64,65 It is quite sensible that the disorder introduced in the layer-by-layer growth at the higher rate produces a slight loss of correlation among the various MLs, sufficient to disrupt the phase matching in the direction perpendicular to the substrate.…”
Section: Two-dimensional Systemssupporting
confidence: 88%